JURIDICAL ANALYSIS IN REVERSE PROOF OF GRATUITIES CASE ACCORDING TO LAW NO. 20 OF 2001 ABOUT CRIMINAL ACTS OF CORRUPTION (Verdict Study No. 86/Pid.sus-TPK/2019/PN MDN) - Gelmok Samosir (NOMOI Law Review, 2022)
The Legal Regulation on Gratification in Law No. 20 of 2001 on Combating Criminal Acts of Corruption is Article 12 B paragraph 1, namely for recipients of gratuities worth Rp 10,000,000 that the burden of proof on the recipient, while more than Rp 10,000,000 the burden of reversal of proof to the Public Prosecutor. The application of Reverse Proof on The Handling of Gratuity Cases 86/Pid.sus-TPK/2019/PN MDN is money amounting to Rp 530,000,000 given to Dzulmi Eldin as Mayor of Medan and the use of money needed operational funds of the Mayor of Medan is used for the purposes of Dzulmi Eldin as Mayor of Medan. The judge in handing down the verdict of Article 5 paragraph 1 of Law No. 31 of 2001 juncto Article 64 paragraph 1 of the Criminal Code is for 2 years and a fine of Rp 200,000,000 with the provision that if the fine is not paid it is replaced with a criminal cage for 4 months. Constraints in the Application of Reverse Proof in The Case of Gratification 86/Pid.sus-TPK/2019/PN MDN do not apply the reverse proof system.Keywords: Reverse Proof, Gratification, Criminal Acts of Corruption